2023
DOI: 10.3892/mmr.2023.12981
|View full text |Cite
|
Sign up to set email alerts
|

VAV3 regulates glioblastoma cell proliferation, migration, invasion and cancer stem‑like cell self‑renewal

Abstract: Glioblastoma multiforme (GBM; World Health Organization grade IV) is one of the most common and aggressive malignant brain tumors and has no effective treatment. Therefore, elucidation of the molecular mechanism of glioma development is very important for finding new therapeutic strategies. The present study evaluated the expression level of Vav guanine nucleotide exchange factor 3 (VAV3) using bioinformatics analysis and demonstrated that VAV3 was overexpressed in human glioblastoma and associated with patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 41 publications
(48 reference statements)
0
4
0
Order By: Relevance
“…The Matrigel-Transwell invasion assay, colony formation investigations, and wound healing assays all demonstrated that the capacity of GBM cells to invade was greatly reduced when GRIK1 was inhibited. The molecular mechanisms of GBM growth and invasion are extremely complex and include many factors, such as lactate dehydrogenases [ 36 ], mitogen-activated protein kinase kinase kinase 1(MAP3K1)/c-JUN signaling-axis [ 37 ], Hsa_circ_0072309 [ 38 ], RNA-binding motif protein 8A (RBM8A) [ 9 ], LINC01711 [ 10 ],COL1A2 [ 11 ], adipocyte enhancer-binding protein 1 (AEBP1) [ 39 ], Nucleobindin-2 [ 40 ], the cross-talk between Notch1 signaling and CXCL12/CXCR4 system [ 41 ], PRL1/USP36/Snail2 axis [ 42 ], Zinc finger CCCH-type containing 15 (ZC3H15) [ 43 ], circ_0060055 [ 44 ], and Rhoj/Rac1/PAK signaling [ 45 ], etc.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The Matrigel-Transwell invasion assay, colony formation investigations, and wound healing assays all demonstrated that the capacity of GBM cells to invade was greatly reduced when GRIK1 was inhibited. The molecular mechanisms of GBM growth and invasion are extremely complex and include many factors, such as lactate dehydrogenases [ 36 ], mitogen-activated protein kinase kinase kinase 1(MAP3K1)/c-JUN signaling-axis [ 37 ], Hsa_circ_0072309 [ 38 ], RNA-binding motif protein 8A (RBM8A) [ 9 ], LINC01711 [ 10 ],COL1A2 [ 11 ], adipocyte enhancer-binding protein 1 (AEBP1) [ 39 ], Nucleobindin-2 [ 40 ], the cross-talk between Notch1 signaling and CXCL12/CXCR4 system [ 41 ], PRL1/USP36/Snail2 axis [ 42 ], Zinc finger CCCH-type containing 15 (ZC3H15) [ 43 ], circ_0060055 [ 44 ], and Rhoj/Rac1/PAK signaling [ 45 ], etc.…”
Section: Discussionmentioning
confidence: 99%
“…Thus, it is important to explore GBM biology and determine new molecular targets relevant to the therapeutic effect. According to recent studies, there are many factors associated with glioma cell growth and invasion, such as Vav guanine nucleotide exchange factor 3 (VAV3) [ 9 ], long noncoding RNA LINC01711 (lncRNA-LINC01711) [ 10 ], collagen alpha-2(I) chain (COL1A2) [ 11 ], NIMA-related kinase 2 (NEK2) [ 12 ], and RAN binding protein 10 (RANBP10) [ 13 ], etc.…”
Section: Introductionmentioning
confidence: 99%
“…All the above four genes were reported to be oncogenic in gliomas. Guo et al discovered that VAV3 can regulate GBM cell proliferation, invasion, and cancer stem-like cell self-renewal [ 36 ]. In addition, RHOC was reported to be involved in the downstream of EGFR signaling, and knock-down RHOC can inhibit EGF-induced VEGF expression [ 37 ].…”
Section: Discussionmentioning
confidence: 99%
“…For example, Mo et al [56] demonstrated that changes in ctDNA may enable us to detect residual disease, guide chemotherapy, stratify risk, and monitor recurrence of stage I to III colorectal cancer. They performed multiplex ctDNA methylation and quantitative polymerase chain reaction assay to detect the ctDNA of six biomarkers (SEPTIN9 locus 1, BCAT1, IKZF1, SEPTIN9 locus 2, VAV3, and BCAN), which in one way or another implicated stem-like or stemness properties, i.e., pluripotency, self-renewal, and differentiation of progenitor stem cells in various tissues [57][58][59][60][61][62].…”
Section: Monitoringmentioning
confidence: 99%